The physics book : from the Big Bang to Quantum Resurrection - Pickover, Clifford A. (Union Square & Co., 2024)
This richly illustrated chronology of physics contains more than 250 short, entertaining, and thought-provoking entries. In addition to exploring such engaging topics as dark energy, parallel universes, the Doppler effect, the God particle, and Maxwell's demon, the book's timeline extends back billions of years to the hypothetical Big Bang and forward trillions of years to a time of "quantum resurrection." This reissue includes four new entries: 2012 (Discovery of the Higgs Boson), 2015 (Gravitational Waves), 2019 (First Image of a Black Hole), and 2023 (Milky Way Neutrino Map). It also features an expanded introduction and updates throughout the book. --